Pemasaran Jasa Pendidikan Sebagai Strategi Peningkataan Minat Sekolah Di Madrasah Aliyah Negeri Insan Cendekia Bangka Tengah - Baryanto Baryanto; Irwan Fathurrochman (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This paper focuses on the marketing of education services by educational institutions which are now facing a lot of challenges in this global era. The marketing of educational serviceis is a strategy to increases school interest for students at this time, which is the most important element for the quality and development of education in an educational institution. The paper will discuss more specifically how marketing is applied in MAN Insan Cendikia Bangka Tengah as a strategy to increase the quality of its education. Furthermore, it look at how widespread marketing of educational services has departed from the original concept of the school as a non-profit institution which is not a business area in the world of education. Schools as providersof educational services need to study and high spiritsto increase school interest for students, becasueeducation is an ongoing teaching learning process.